Produtividade e qualidade industrial de trigo em diferentes anos e regiões de cultivo - Schidlowski, Lucas Leonardo (2014)
The productivity and technological quality of wheat is influenced by genetic, environmental and management factors. The environmental contribution in the definition of component traits of yield and quality attributes of flour requires extensive evaluation of genotypes in multiple locations for years. The objective of this study was to evaluate the effect of years (2007-2011) and growing regions (Abelardo Luz- SC , Cascavel - PR, Castro - PR, Guarapuava - PR , Não-Me-Toque - RS and Palotina - PR) on the quality industrial and grain yield in sets of trials of wheat ( Triticum aestivum L.), with a view to recommending cultivars and identification of regions that maximize the quality of baking. Analyses of joint variance and calculated statistical comparison of means , association between character and adaptability and stability of genotypes to different growing regions, using graphical GGE Biplot analysis and AMMI analysis were performed. The results indicate that all traits were influenced by genotype (G), environment (E) interaction GxE. The determinants of quality characters of wheat bread have their phenotypic variation mainly controlled by genetic effects. The CD 150, CD 108 and IPR 85 cultivars showed excellent behavior in relation to baking quality. The test environment Não-Me-Toque is ideal for selection of genotypes with a focus on yield and hectoliter mass. Ideal environments for the selection of genotypes with a focus on quality of bread making, in order, Abelardo Luz, Cascavel and Guarapuava.